Molecular Docking Studies and In Vitro Activity of Paliurus spina-christi Mill Extracts as Pancreatic Lipase Inhibitors - Fedora Grande; Mariangela Marrelli; Valentina Amodeo; Maria Antonietta Occhiuzzi; Iulia Pinzaru; Mary Fucile; Cristina Adriana Dehelean; Ersilia Alexa; Filomena Conforti; Giancarlo Statti (MDPI AG, 2024)
Obesity is a risk factor for the onset of chronic diseases. One of the most promising approaches to treating obesity consists of reducing dietary fat absorption using extracts from plants because they contain phenolic compounds, especially flavonoids. Paliurus spina-christi, belonging to the Rhamnaceae family, is one of the five species belonging to the Paliurus genus. Herein, the aerial parts of the plant were extracted with methanol through the pressurized cyclic solid-liquid extraction using the Naviglio extractor®. The extracts were analyzed with High Performance Thin Layer Chromatography and investigated for their in vitro biological potential. The phytochemical analysis revealed that rutin has been shown to be the most abundant flavonoid component. The best antiradical activity was observed for the fruit extract with an IC50 value of 53.41 ± 1.24 µg/mL. This extract also has a better inhibitory capacity on lipid peroxidation evaluated at a different time of incubation. Potent lipase inhibitor activity of the extract from fruits was also demonstrated with in vitro experiments. This property can be attributed to a direct interaction of main components of P. spina-christi extract with the human pancreatic enzyme as demonstrated by the results of molecular docking experiments conducted on the crystallographic structures of lipase.